Caffeine controversies. Issue 2 (April 2018) - Gentle, Samuel J.; Travers, Colm P.; Carlo, Waldemar A.
Abstract : Purpose of review: Caffeine use in preterm infants has endured several paradigms: from standard of care to possible neurotoxin to one of the few medications for which there is evidence of bronchopulmonary dysplasia (BPD) risk reduction. The purpose of the review is to analyze this dynamic trajectory and discuss controversies that still remain after decades of caffeine use. Recent findings: Following concerns for caffeine safety in preterm infants, a large randomized controlled trial demonstrated a reduction in BPD and treatment for patent ductus arteriosus. The lower rate of death or neurodevelopmental impairment noted at 18–21 months was not statistically different at later timepoints; however, infants in the caffeine group had lower rates of motor impairment at 11-year follow-up. The time of caffeine therapy initiation is now substantially earlier, and doses used are sometimes higher that previously used, but there are limited data to support these practices. Summary: Caffeine therapy for apnea of prematurity (AOP) remains one of the pillars of neonatal care, although more evidence to support dosing and timing of initiation and discontinuation are needed.